2012
DOI: 10.1007/s00216-012-5748-6
|View full text |Cite
|
Sign up to set email alerts
|

Probing substrate–product relationships by natural abundance deuterium 2D NMR spectroscopy in liquid-crystalline solvents: epoxidation of linoleate to vernoleate by two different plant enzymes

Abstract: Natural abundance deuterium 2D NMR spectroscopy in weakly ordering, polypeptide chiral liquid crystals is a powerful technique that enables determination of enantiotopic isotopic ratios ((2)H/(1)H)( i ) at the methylene groups of long-chain fatty acids. This technique has been used to study the bioconversion of linoleic acid to vernoleic acid with the objective of establishing the in-vivo site-specific fractionation of (2)H associated with this process. The fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In this application work, the relative variations in the site-specific natural distribution of 2 H were determined to ascertain whether distinct features of the reaction center could be recorded in the ( 2 H/ 1 H) i isotopic ratios of the substrate and the product. 195 Although E. lagascae and V. galamensis use different enzymes to carry out the D 12 -epoxidation of linoleate to vernoleate: a cytochrome P450 monooxygenase in the former and a di-iron dioxygenase in the latter, it was evidenced that the linoleate and vernoleate isolated from the seed oils of the two plants show remarkably similar isotope profiles, with selection against 2 H in the positions around the D 12 -epoxidation site. Such a similarity was interpreted as indicating that the dominant feature of the reaction mechanism is the involvement of the activated Fe, while the architecture of the active site is less important.…”
Section: ( 2 H/ 1 H) Isotope Fractionation In Biocompoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this application work, the relative variations in the site-specific natural distribution of 2 H were determined to ascertain whether distinct features of the reaction center could be recorded in the ( 2 H/ 1 H) i isotopic ratios of the substrate and the product. 195 Although E. lagascae and V. galamensis use different enzymes to carry out the D 12 -epoxidation of linoleate to vernoleate: a cytochrome P450 monooxygenase in the former and a di-iron dioxygenase in the latter, it was evidenced that the linoleate and vernoleate isolated from the seed oils of the two plants show remarkably similar isotope profiles, with selection against 2 H in the positions around the D 12 -epoxidation site. Such a similarity was interpreted as indicating that the dominant feature of the reaction mechanism is the involvement of the activated Fe, while the architecture of the active site is less important.…”
Section: ( 2 H/ 1 H) Isotope Fractionation In Biocompoundsmentioning
confidence: 99%
“…Such a similarity was interpreted as indicating that the dominant feature of the reaction mechanism is the involvement of the activated Fe, while the architecture of the active site is less important. 195…”
Section: ( 2 H/ 1 H) Isotope Fractionation In Biocompoundsmentioning
confidence: 99%
“…[27][28][29][30][31][32] Furthermore, this method has recently provided precious insights into the natural site-specic ( 2 H/ 1 H) isotopic fractionation of bioproducts, including (un)saturated fatty acids and triglycerides. [33][34][35][36][37][38] NAD NMR detection offers many advantages. First of all, it avoids the 2 H isotope labeling, which is oen burdensome and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…30,32,42,43 Currently the most employed methods in the frame of analytical applications are the Q-COSY Fz and Q-resolved Fz 2D experiments, which permit the two components of various quadrupolar doublets to be correlated and then permit to assign them on the basis of the anisotropic 2 H chemical shis, d aniso ( 2 H). 36,39,44 One of the major limitations of NAD NMR is its low intrinsic sensitivity owing to the low gyromagnetic ratio (g( 1 H)/g( 2 H) z 6.515) and the low natural abundance of the deuterium isotope (V-SMOW ¼ 1.5 Â 10 À2 %). [30][31][32]45 Furthermore, the duration of NAD 2D-NMR experiments can be limited to 15-20 h by the stability of the mesophase and the dri of the static magnetic eld, B 0 , in the absence of 2 H spin lock.…”
Section: Introductionmentioning
confidence: 99%
“…The approach was successively tested on polyunsaturated C‐18 fatty acid methyl esters and then applied to C‐14 to C‐18 saturated fatty acid methyl esters (SAFAs) . The power of this emerging approach for biochemical studies has been nicely demonstrated recently . Compared with the SNIF‐NMR® technique developed by Martin and co‐workers in 1980s that uses isotropic liquids as NMR solvent, NAD NMR spectroscopy in polypeptide‐oriented solvents has three advantages: (i) the 2 H quadrupolar interaction is no longer averaged to zero as in liquids, and hence each inequivalent deuterium site gives rise to a quadrupolar doublet (QD) whose splitting, Δν Q , is proportional to the order parameter of the C–D bond, S C–D , (where centercenterΔvQ=32KCDSCDcenterwithcenterSCD=a,bSabcosθaCDcosθbCD); (ii) the distribution of doublets on NAD 2D maps allows to reduce the peak overlapping for small‐to‐middle size molecules and generally provides different QDs for fortuitously isochronous deuterons unlike to isotropic NMR for which resonances are located at the same 2 H chemical shift; and (iii) the spectral discrimination of enantiotopic elements in prochiral molecules or enantiomers is possible when the mesophase is chiral …”
Section: Introductionmentioning
confidence: 99%